2021
DOI: 10.1049/hve2.12099
|View full text |Cite
|
Sign up to set email alerts
|

Simulations and experiments of the generation apparatus of the DC electric field with the space charge

Abstract: To make accurate measurements, field mills must be calibrated in a known DC electric field space charge in which the quantities can be control1ed. A simulation model of the generation apparatus of the electric field with a space charge has been built. Based on the combination of the electric field and the transfer of a dilute substances model, the influence of openings in the metal screen was calculated. Simulation results showed that the opening size of the high-voltage electrode has a great influence on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…For other types of wires, the charge density in the air is between 10 −6 C/m 3 and 10 −9 C/m 3 according to the calculated ion flow field. The mobility of positive and negative ions is generally 1.4 to 3.8 × 10 −4 m 2 /(V⋅s) [30], so the 'equivalent conductivity' in the air is generally of the order of 10 −13 to 10 −10 . On the other hand, according to the actual measurements of the ground electric field strength, the amplitude of the space charge-modified electric field is generally 5 to 20 kV/m, and the ion current density is generally 10 to 50 nA/m 2 [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For other types of wires, the charge density in the air is between 10 −6 C/m 3 and 10 −9 C/m 3 according to the calculated ion flow field. The mobility of positive and negative ions is generally 1.4 to 3.8 × 10 −4 m 2 /(V⋅s) [30], so the 'equivalent conductivity' in the air is generally of the order of 10 −13 to 10 −10 . On the other hand, according to the actual measurements of the ground electric field strength, the amplitude of the space charge-modified electric field is generally 5 to 20 kV/m, and the ion current density is generally 10 to 50 nA/m 2 [31].…”
Section: Discussionmentioning
confidence: 99%
“…In view of the measurement error caused by ion current, Zhang et al used a DC electric field measurement device [17], adopted the differential input method to reduce the interference of the ion signal of the field mill, and improved the measurement accuracy [18]. Wang et al discussed whether the cover plate can be removed [19], and found that the electric field distortion coefficient was a fixed value when the cover plate was added or not, and the measurement results were similar after calibration. Zhao et al conducted three-dimensional finite element simulation and actual measurement, discussed the differences between the three methods of the measuring conditions and proposed corresponding calibration methods for each method [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to ensure the safety of experiments, the breakdown electric field strength of composites under the AC electric field is tested first. Weibull distribution [40,41] is used to process the breakdown electric field strength data and shown in equation (2).…”
Section: Relationship Between Electroluminescence Intensity and Elect...mentioning
confidence: 99%
“…With the rapid development of the smart grid, advanced electric field measurement technology is increasingly required, which is one of the most significant segments to ensure the normal operation of power equipment [1,2]. The amplitude and frequency composition of an electric field becomes more complex accompanied by the introduction of a large number of power electronic devices [3].…”
Section: Introductionmentioning
confidence: 99%